Ricinus communis treatment of denture stomatitis in institutionalised elderly - Pinelli, Ligia Antunes Pereira [UNESP]; Montandon, Andréia Affonso Barretto [UNESP]; Corbi, S. C T [UNESP]; Moraes, T. A. [UNESP]; Fais, L. M G [UNESP] (Wiley, 2013)
This study compared the effectiveness of Ricinus communis (RC) with Nystatin (NYS) and Miconazole (MIC) in the treatment of institutionalised elderly with denture stomatitis (DS). They (n = 30) were randomly distributed into three groups: MIC, NYS or RC. Clinical and mycological evaluations were performed prior to the use of the antifungal (baseline) and repeated after 15 and 30 days of treatment. The sample was clinically examined for oral mucosal conditions. Standard photographs were taken of the palate, and the oral candidiasis was classified (Newton's criteria). Mycological investigation was performed by swabbing the palatal mucosa, and Candida spp. were quantified by counting the number of colony-forming units (cfu mL-1). The clinical and mycological data were analysed, respectively by Wilcoxon and Student's t-test (α = 0·05). Significant improvement in the clinical appearance of DS in the MIC and RC groups was observed between the 1st and 3rd collections (MIC - P = 0·018; RC - P = 0·011) as well as between the 2nd and 3rd collections (MIC - P = 0·018; RC - P = 0·011). Neither groups showed a statistically significant reduction in cfu mL-1 at any time. Although none of the treatments decreased the cfu mL-1, it was concluded that Ricinus communis can improve the clinical condition of denture stomatitis in institutionalised elderly patients, showing similar results to Miconazole. © 2013 Blackwell Publishing Ltd.
Keywords: Candidiasis; Dental care for aged; Health of the elderly; Homes for the aged; Ricinus communis